“Detik-Detik diselamatkannya Jo” Studi Konten Pesan Iklan Youtube #GoPaydiNetflix terhadap Digital Video Ads (DVAs) - Muhammad Zahid; Kurnia (UNISBA Press, 2023)
Abstract. Advertising uses social media as an advertising strategy. This research discusses specifically about Digital Video Ads Value in providing Gopay product information to the public in increasing Netflix subscription payments through Gopay. This study aims to examine the value in Gopay's advertisement entitled